La presidencia acorralada de Enrique Peña Nieto - Loaeza, Soledad (El Colegio de México A.C., 2020)
This article analyzes the presidency of Enrique Peña Nieto in the broader context of the transformations undergone by Mexican presidentialism as the result of the opening up of the political system and the growing plurality, particularly since the 1990s. The central hypothesis is that the process of dismantling the authoritarian state and structural reforms took away powers from the Office of the President to intervene in politics and the economy. The principal consequence of these changes was the weakening of the Executive power, the growing influence of private interests and a shift towards a focus on the personality of the president.These tendencies were expressed in a particular manner during Peña Nieto’s term in office, revealing the Executive’s lack of strength. This article examines in detail the process and the dynamics that led to this reconfiguration of the Mexican presidency, and highlights the resulting effects during the 2012-2018 administration, particularly with regard to the difficulty of containing criminal violence and corruption, as well as the personalization of the position of president.